Digitalisasi PT Pos dalam Meningkatkan Kepuasan Pelanggan PT Pos Indonesia - Lisawanto Lisawanto; Yaya Mulya Mantri; Ramayani Yusuf; Mohdari Mohdari (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the impact of service digitization reform on customer satisfaction in PT Pos Indonesiaa Bandung City Office. This digitization reform will affect PT Pos activities as a whole because technological developments are inevitable. Digital service operations will affect customer satisfaction, with such digitalization, customers can feel satisfied and vice versa. The number of respondents in this study was 100 using random sampling method. This study uses a quantitative method with data collection methods using a Likert scale questionnaire that tests the independent variables and the dependent variable using simple linear regression analysis to measure measurement accuracy using validity and reliability tests. The processing results showed that service digitalization reform and customer satisfaction are in the "good" category. The digitization reform of PT Pos has a good impact and makes customers feel satisfied. This research can be developed by studying other issues related to other reforms carried out in PT Pos Indonesia so that it becomes a new strength for PT Pos Indonesia.